Assessing and improving the efficiencies of a steam power plant using exergy analysis. Part 2: improvements from modifying reheat pressure. (12th July 2006) - Rosen, Marc A.; Tang, Raymond
The effect of increasing reheat pressure on the exergy efficiency of a coal-fired steam power plant is investigated. The results show that although the irreversibility rate associated with heat transfer in the steam generator decreases as reheat pressure increases, the overall-plant exergy efficiency decreases, mainly owing to the relatively large decrease in shaft power output. The results suggest, therefore, that investigations into the effect of decreasing reheat pressure may be merited.